Digitalization of MSMEs: Market Expansion and Business Efficiency Through Technology in Sabila Village, Mallawa District, Indonesia - Nurhaeda Zaeni; Muhammad Rijal; M. Maryadi; Hamdana Jamaluddin; Hikmah Manganni; Musdhalifah Yusran (Golden Ratio of Community Services and Dedication, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in strengthening local economies and creating employment opportunities. However, many MSMEs still face limitations in digital literacy, market access, and business management efficiency. This community service activity aimed to enhance MSME capacity through an entrepreneurship seminar focusing on digitalization. The seminar was conducted in Sabila Village, Mallawa District, Maros Regency, involving 40 MSME actors from various business sectors. The activity employed a participatory andragogical approach consisting of interactive presentations, group discussions, and practical demonstrations. The results indicate that participants experienced increased understanding of digital marketing strategies, improved awareness of online marketplace utilization, and enhanced motivation to adopt technology for business efficiency. The seminar also facilitated collaboration among MSME actors and generated practical strategies for market expansion. The findings confirm that digital entrepreneurship seminars serve as effective tools for MSME empowerment and contribute to sustainable local economic development.